معلّم اللغة العربية للناطقين بغيرها المؤهّلات والمهارات - مناعي, البشير (جامعة الوادي - university of Eloued, 2018)
هذه قراءة وصفية تحليلية تقف على أهمية اختيار المعلّم الكفء لتدريس اللغة العربية لغير الناطقين بها، وهذا لغاية تحديد أهمّ المؤهلات والمهارات الواجب توافرها فيه لغاية أساسية وهي تحقيق النجاعة في العملية التعليمية ذات الصلة بهذه الفئة، وذلك لما تكتسيه العملية من حساسية بالغة بسبب الفئة المستهدفة بالدراسة ، وبسبب تنوّع أنشطة معلّم اللغة العربية وتعّددها ، بالإضافة إلى الطرق التربوية الحديثة والتي يؤكّد مختصّوها على ضرورة مراعاتها في تكوين فعّال لمتعلّمي اللغة العربية من الناطقين بغيرها. Abstract: This is an analytical and descriptive study that emphasizes the importance of selecting an efficient teacher to teach Arabic to non-native speakers. The purpose of the paper is to determine the most important required qualifications and skills that ensure efficiency in the educational process related to this group because of the diversity of activities of the Arabic language teacher, in addition to that the use of the modern educational methods, which, as the specialists said, need to be used in order to realize an effective teaching for the non-native Arabic learners.
مقال
Keywords: معلّم اللغة العربية؛ الناطقون؛ بغيرها ؛ المؤهّلات ؛ المهارات